Preparation and Characterization of a new plasticized polymer electrolyte for "all solid state" Zn/MnO2 cell - Z. Gharnout; L. Telli; A. Merrouche; L. Zerroual; S.Walter (Université de M'sila, 2021)
A solid polymer electrolyte with a polyvinyl alcohol (PVA) matrix and a mixture of ethylene glycol (EG) and phosphoric acid as proton conductor has been developed. These complexes have been studied by X-ray diffraction (XRD), infrared Fourier transform spectrometry (FTIR) and electrochemical impedance spectrometry (EIS).The optimum ionic conductivity value of the ternary PVA-EG(45 wt.%)-H3PO4(5 wt.%) complex film has been achieved to be 5.2 10-3 S cm-1 at RH = 100% with adequate mechanical properties (especially flexibility) and with a low activation energy of 9 kJ mol-1. Due to their good electrical as well as mechanical properties, such material has been successfully used as solid state protonic electrolyte in Zn/MnO2 cell with a capacity of 220Ahkg-1andan energy density up to 286 Wh kg-